AN ANALYSIS OF GENDER AND MARGINALITY IN DANCE LIKE A MAN OF MAHESH DATTANI - Mandal, Partha Sarathi; Yadav, Ravi Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With its origins in the state of Tamil Nadu in southern India, the ancient Indian classical dance style known as Bharatanatyam first emerged. There was a time when devadasis, who were prostitutes, were the ones who carried it out in royal courts. After some time has passed, the ruling elite in India starts to consider it more like a commodity, making a distinction between it and devadasis. Within patriarchal societies, the passion that a man has for artistic expression can cause a great deal of friction. Many people have doubts about his manhood and hold him in lesser regard than the idealized picture of what it means to be a man. As a result of women deviating from the conventional gender roles that are expected of them in society, patriarchy produces discord. Dance Like a Man is a drama written by Mahesh Dattani that addresses a variety of problems, including identity crises, prejudice, gender standards, and gender stereotypes. To tell the truth, there is a dearth of fruitful debate regarding the challenges that men confront as a consequence of prejudice based on their gender. An attempt is made to portray a male victim of sexism through the play’s protagonist, Jairaj. The purpose of this research is to analyze the ways in which society reinforces gender stereotypes, whether there are problems with reversing gender roles, and whether there are doubts concerning masculinity. The character of Jairaj is used in this play in an effort to paint a more accurate picture of a male victim of gender prejudice. In the current study, the issues that arise when attempting to reverse gender norms, the question of what it means to be masculine, and the role that society plays in perpetuating gender stereotypes are investigated.